PENGATURAN KEWENANGAN KANTOR OTORITAS BANDAR UDARA DALAM PELAKSANAAN PENGAWASAN BANDARA MENURUT UNDANGUNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN (Studi Bandar Udara Minangkabau) - Prasetya, Doni (LPPM Universitas Ekasakti Padang, 2019)
Aviation security and safety has an important and strategic role in flight management, so that its operation is controlled by the State of Coaching carried out by the government in a unified civil aviation security and safety service system. Law No. 1 of 2009 concerning Aviation is to improve the surveillance system for airlines, including flight operators. In carrying out its duties, namely ensuring the level of suitability of the operator's application with applicable international rules. Therefore, the Minister of Transportation Regulation No. PM 41 of 2011 was formed concerning the Organization and Work Procedures of the Office of the Airport Authority (Minister of Agriculture Regulation No. 41 of 2011). This Ministerial Regulation changes the procedures of the previous organization, namely the Airport Administrator Office. This is an effort to realize the flight operations that are safe, secure, fast, smooth, orderly and integrated and integrated with other modes of transportation. Based on the results of the discussion and analysis it can be concluded that the Airport Authority Office of Region VI Padang as the Technical Implementation Unit, in the supervision function has become the duty and responsibility to monitor all activities of airport aerialism. In accordance with the regulations applicable, the Office of the VI - Padang Airport Authority conducts programs such as conducting field monitoring, conducting inspections, conducting Ramp checks and socializing the community and elements related to the latest regulations on aviation. The obstacles found in the implementation of the authority of the Airport Authority Office in the implementation of airport supervision there are still negligent / careless airline operators to follow up on issues found in the field which is a great potential that can threaten aviation safety and flight security. It still lows the fulfillment of the quality and quantity of Flight Inspectors and administrative officers at the Office of the Airport Authority. HR of both quality and quantity is still inadequate in carrying out its duties and functions.